Non-uniform Response to Temozolomide Therapy in a Pituitary Gonadotroph Adenoma (2014)
ABSTRACT: Endocrinologically active pituitary adenomas are treated either with surgery, radiotherapy or various drugs, including dopamine agonists, long-acting somatostatin analogs, growth hormone receptor antagonists, or corticosteroid secretion inhibitors. Fully 35% to 55% of pituitary adenomas invade adjacent structures. This figure is lower in gonadotroph adenomas, less than 5% compared to other adenoma types. Clinical management of invasive adenomas is challenging, and most of them tend to recur after surgery.